2013
DOI: 10.1039/c3ta12036h
|View full text |Cite
|
Sign up to set email alerts
|

Single-crystal FeFe(CN)6 nanoparticles: a high capacity and high rate cathode for Na-ion batteries

Abstract: Prussian blue analogues are actively explored as low cost and high capacity cathodes for Na ion batteries; however, their applications are hindered by low capacity utilization and poor cyclability of these compounds. Here we show that this problem can be solved by controlling the purity and crystallinity of the Prussian blue lattices. As a model compound, single-crystal Fe III Fe III (CN) 6 nanoparticles are synthesized and found to have a sufficiently high capacity of 120 mA h g À1 , an exceptional rate capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
254
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 321 publications
(267 citation statements)
references
References 30 publications
10
254
0
3
Order By: Relevance
“…3(b). Owing to the structural imperfection and abnormal cationic arrangement of the PBC lattices, the Na + insertion/extraction process in the PBC may lead to a large volume variation to accommodate the structural change [24]. However, PBN exhibits a low mechanical strain, leading to more stable cycling performance.…”
Section: Resultsmentioning
confidence: 99%
“…3(b). Owing to the structural imperfection and abnormal cationic arrangement of the PBC lattices, the Na + insertion/extraction process in the PBC may lead to a large volume variation to accommodate the structural change [24]. However, PBN exhibits a low mechanical strain, leading to more stable cycling performance.…”
Section: Resultsmentioning
confidence: 99%
“…FeFe(CN)6 had good cycling stability with a slight capacity decay from the initial 120 to 115 mAh g -1 after 150 cycles, 18 and Goodenough's group also suggested that KFeFe(CN)6 exhibits excellent capacity retention of more than 99% after 30 cycles. 15 A fatal flaw, however, is that…”
mentioning
confidence: 88%
“…[ 237 ] In addition, the highly crystalline NaFe 2 (CN) 6 /graphene composite delivered a discharge capacity of 150 mA h g −1 with an energy density of 280 Wh kg −1 . [ 238 ] The family of alkali-ion-defi cient cubic AM II Fe III (CN) 6 (A = Na or K) compounds requires a presodiation process to be combined with conventional Na-free anodes; otherwise, the electrode operation undergoes only one electron transfer with Fe 3+ /Fe 2+ redox couples, resulting in a low capacity below 70 mA h g −1 .…”
Section: (16 Of 38)mentioning
confidence: 99%